Three new species of Anacroneuria Klapálek (Plecoptera: Perlidae) from Panama - Gutiérrez-Fonseca, Pablo E. (Zootaxa, 2015)
In Central America, the Plecoptera is represented by the genera Anacroneuria and Perlesta, both from the Perlidae family. A total of 45 species have been reported for the region, of which 16 have been found in Panama, all of the genus Anacroneuria. Three new species for Panama are described in this study: Anacroneuria darien, A. embera, and A. laru.